A retrospective chart review study to quantify the monthly medical resource use and costs of treating patients with treatment resistant depression in the United Kingdom. (1st February 2021) - Denee, Tom; Ming, Timothy; Waller, John; Bailey, Tom; Rajkovic-Hooley, Olivera; Middleton-Dalby, Chloe; Le, Hoa H.; Zhang, Qiaoyi; McCrone, Paul; Taylor, David
Abstract: Introduction: Major depressive disorder (MDD) is a globally prevalent chronic psychiatric illness with a significant disease impact. As many as 30% of patients with MDD do not adequately respond to two therapies and are considered to be treatment resistant. This study aimed to quantify healthcare costs associated with treatment resistant depression (TRD) in the UK. Methods: A retrospective chart review of patients with TRD was conducted in primary and secondary care settings over a 2 year period. Data abstracted from medical records of patients included demographics, clinical characteristics and healthcare resource utilization (HCRU; number of consultations, use of Crisis Resolution and Home Treatment Teams [CRHTTs], non-drug and drug interventions, and hospitalizations). HCRU per patient per month (28 days) was calculated for three health states: major depressive episode (MDE), remission and recovery. Unit costs were from the British National Formulary (BNF) and the Personal Social Services Research Unit (PSSRU). Results: A total of 295 patients with TRD were recruited between January 2016 and May 2018. The mean age of the total sample was 43.3 years; 60.3% were female. Costs per patient, per 28 days, were highest in the MDE state, with the average cost (£992) mainly driven by consultations, non-drug treatment, hospitalizations and CRHTT, with a considerable fall in costs as patients moved into remission and subsequent recovery. Conclusion: The results suggest that antidepressant treatments for TRD that are more effective in reducing the time spent in an MDE health state, and helping patients achieve remission and recovery, are essential for reducing the overall HCRU and costs in patients with TRD. Cost of TRD in the UK Strengths and limitations of this study: This observational study of TRD is the first to assess the HCRU impact associated with different predefined health states. Using retrospective data from both primary and secondary care physicians from regions across the UK ensures a representative real-world patient population. One limitation is that the selection of patients is based on criteria that define TRD that rely on physician judgement. Although the study captures direct HCRU costs, the indirect costs of lost productivity and care are not included in the overall burden. This study has defined the current clinical management of patients with TRD in the UK and provides an estimate of the associated HCRU and associated costs.